Gross anatomy and histology of alimentary system of stick insect, Pylaemenes mitratus (Phasmid: Basillidae) - Mohamad Harris Nasir; Azman S.; Nurul Wahida O. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The gross anatomy and histology of the alimentary tract of the stick insect, Pylaemenes mitratus were described in this study. Three distinct part of its alimentary system were investigated; the foregut, midgut and hindgut were observed. The foregut consists of oesophagus, crop and proventriculus. The inner most layer of foregut and hindgut show an intima which has a chitinous layers and folded along the epithelium cell at the hindgut. The external of the gut surrounded by muscularis made up of circular muscle and longitudinal muscle. The midgut is made up of gastric caecum whereas ventriculus. The histology structure consists of epithelium layer of endoderm cells that secrete digestive enzyme and site for absorption of food nutrient. The hindgut starts at Malpighian tubule to the ileum, rectum and ends at the opening of anus as a place for faecal excretion.